Repeated cold exposures protect a mouse model of Alzheimer's disease against cold-induced tau phosphorylation - Marine Tournissac; Philippe Bourassa; Ruben D. Martinez-Cano; Tra-My Vu; Sébastien S. Hébert; Emmanuel Planel; Frédéric Calon (Elsevier, 2019)
Objective: Old age is associated with a rise in the incidence of Alzheimer's disease (AD) but also with thermoregulatory deficits. Indicative of a link between the two, hypothermia induces tau hyperphosphorylation. The 3xTg-AD mouse model not only develops tau and amyloid pathologies in the brain but also metabolic and thermoregulatory deficits. Brown adipose tissue (BAT) is the main thermogenic driver in mammals, and its stimulation counteracts metabolic deficits in rodents and humans. We thus investigated whether BAT stimulation impedes AD neuropathology. Methods: 15-month-old 3xTg-AD mice were subjected to repeated short cold exposures (RSCE), consisting of 4-hour sessions of cold exposure (4 °C), five times per week for four weeks, compared to animals kept at housing temperature. Results: First, we confirmed that 3xTg-AD RSCE-trained mice exhibited BAT thermogenesis and improved glucose tolerance. RSCE-trained mice were completely resistant to tau hyperphosphorylation in the hippocampus induced by a 24-hour cold challenge. Finally, RSCE increased plasma levels of fibroblast growth factor 21 (FGF21), a batokine, which inversely correlated with hippocampal tau phosphorylation. Conclusions: Overall, BAT stimulation through RSCE improved metabolic deficits and completely blocked cold-induced tau hyperphosphorylation in the 3xTg-AD mouse model of AD neuropathology. These results suggest that improving thermogenesis could exert a therapeutic effect in AD. Keywords: Alzheimer's disease, brown adipose tissue, tau phosphorylation, thermoregulation, 3xTg-AD mice